Naja atra venom-spit ophthalmia in Taiwan: An epidemiological survey from 1990 to 2016. Issue 1 (January 2020) - Tsai, Tsung-Han; Lin, Chun-Chi; Mao, Yan-Chiao; Hung, Chia-Lien; Yang, Yi-Chiang; Yang, Chen-Chang; Jeng, Mei-Jy
Abstract : Background: Venomous snakebites are common during hot seasons in Taiwan. However, rarely is venom spat directly into the subject's eyes, causing eye injury. Despite being uncommon, analytical data regarding venom-spit ophthalmia in Taiwan have been lacking. This study thus aimed to conduct an epidemiological survey on Naja atra venom-spit ophthalmia in Taiwan during the past decades to improve future care of such patients. Methods: Registered records of cases with snake venom injuries at the Taiwan National Poison Control Center from 1990 to 2016 were retrospectively reviewed, enrolling those with records of cobra venom-spit eye injuries and excluding exotic species. Demographic data, clinical symptoms, snake species, ocular conditions, management, and outcomes were recorded and analyzed. Results: A total of 39 cases suffering from Naja atra venom-spit ophthalmia were enrolled. The overall incidence rate was 1.6 cases per million people from 1990 to 2016. Among the included cases, most were unilaterally injured (82%), male (95%), aged 18 to 59 years (90%), injured during catching (51%), and injured in spring and summer (92%). Ocular symptoms occurred in 90% of the cases, majority of which included ocular pain (90%) and redness (85%). Conjunctivitis (67%) and corneal injury (59%) of involved eyes were common. Immediate water irrigations were done in all cases, most of whom received further topical eye drops, including antibiotics, corticosteroids, and vasoconstrictors. Although topical or intravenous antivenoms were administered in 11 cases, no obviously superior outcome was observed. Most cases (77%) were symptom free after the acute stage. Conclusion: Although Naja atra venom-spit ophthalmia in Taiwan is uncommon, the risk for transient ocular symptoms and corneal/conjunctival injury does exists. Prompt ocular irrigation and professional ophthalmic care after envenomation help prevent serious ocular sequelae. Moreover, superior outcomes were not achieved with the use of antivenom. Nonetheless, further studies are required to clarify the role antivenoms play in venom-spit ophthalmia.